2017
DOI: 10.7448/ias.20.01.21678
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir–lamivudine as initial therapy in HIV‐1 infected, ARV‐naive patients, 48‐week results of the PADDLE (Pilot Antiretroviral Design with Dolutegravir LamivudinE) study

Abstract: Introduction: A proof-of-concept study was designed to evaluate the antiviral efficacy, safety and tolerability of a two-drug regimen with dolutegravir 50 mg once daily (QD) plus lamivudine 300 mg once daily as initial highly active antiretroviral therapy (HAART) among antiretroviral (ARV)-naive patients.Methods: PADDLE is a pilot study including 20 treatment-naive adults. To be selected, participants had no IAS-USA-defined resistance, HIV-1 RNA ≤100,000 copies/mL at screening and negative HBsAg. Plasma viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 34 publications
5
70
0
2
Order By: Relevance
“…While preliminary analyses of a Dutch DTG monotherapy simplification trial seemed encouraging at 24 weeks, rates of virological failures increased significantly by week 48, suggesting a sub-optimal potency of this regimen 8 . On the other hand, several studies evaluating DTG-based dual therapy with either 3TC or rilpivirine (RPV), showed a high virological efficacy 9– 12 . However, most reports were from small, observational cohort studies, with the exception of one DTG-RPV industry-sponsored randomized controlled trial (RCT) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…While preliminary analyses of a Dutch DTG monotherapy simplification trial seemed encouraging at 24 weeks, rates of virological failures increased significantly by week 48, suggesting a sub-optimal potency of this regimen 8 . On the other hand, several studies evaluating DTG-based dual therapy with either 3TC or rilpivirine (RPV), showed a high virological efficacy 9– 12 . However, most reports were from small, observational cohort studies, with the exception of one DTG-RPV industry-sponsored randomized controlled trial (RCT) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…21 In particular, lamivudine is eliminated by filtration and active renal tubular secretion. 24,25 The GEMINI studies compared once-daily coadministration of 50 mg dolutegravir plus 300 mg lamivudine to a standard of care, once-daily, 3-drug regimen consisting of a 50-mg dolutegravir tablet plus a 2-drug, fixed-dose tablet containing 300 mg tenofovir disoproxil fumarate and 200 mg emtricitabine. In peripheral blood mononuclear cells, lamivudine is anabolized by phosphorylation to lamivudine triphosphate, the molecule required for antiviral activity.…”
mentioning
confidence: 99%
“…19 Metabolism is a minor route of elimination, with only 5% to 10% of the parent drug metabolized to an inactive transsulfoxide metabolite that is excreted in the urine. 24,25 To pursue new fixed-dose tablet formulations, development was initiated for a 2-drug single tablet containing 50 mg dolutegravir and 300 mg lamivudine. 18 Lamivudine has demonstrated few interactions with cytochrome P450 enzymes, although drugs that are also renally excreted have the potential for interactions with lamivudine.…”
mentioning
confidence: 99%
“…Currently, numerous recent trials have evaluated the use of two‐drug regimens to reduce toxicities, both in treatment‐naïve and in pretreated patients. The benefits of switching to an NRTI‐sparing regimen from E/C/F/TAF must be balanced against potential detriments: disruption of the single‐tablet regimen and increases in the number of pills and drug intake , changes in lipid parameters that may necessitate additional monitoring or treatment, persistence of viral replication in reservoir sites such as the central nervous system (CNS) , and absence of activity against hepatitis B virus (HBV). Only randomized clinical trials can definitively assess safety and efficacy differences between E/C/F/TAF and NRTI‐sparing regimens.…”
Section: Discussionmentioning
confidence: 99%